Phase engineering and surface reconstruction of CrₓMnFeNi high entropy alloys for electrocatalytic water splitting - Wang, Yong (2023)
The quest for cost-effective and efficient catalysts for oxygen and hydrogen evolution reactions is vital for a carbon-neutral future. High entropy alloys (HEAs), known for their exceptional thermodynamic stability and performance, have recently emerged as promising candidates in this field. Yet, the relationship between the phase and catalytic performance in HEAs remains understudied. Commonly, metallic catalysts undergo surface reconstruction under high oxidizing potentials under the oxygen evolution reaction (OER), making the identification of the truly active species essential for designing efficient catalysts. Nonetheless, characterization of surface reconstruction of nanoscale HEAs is challenging due to low content of each metal, exacerbated by the use of nonmetal support during synthesis. In this study, we unveil the phase-performance relationship in HEAs and identify that the body-centered cubic (BCC) phase CrMnFeNi outperforms its face-center cubic (FCC) phase counterparts in catalyzing both OER and the hydrogen evolution reaction (HER) due to its superior electrical conductivity and optimized electronic structures. Particularly, Cr1.5MnFeNi with the most prominent BCC phase demonstrates superior OER activity (η10 of 255 mV and Tafel slope of 28.7 mV dec−1), surpassing other Cr, Mn, Fe, Ni-based catalysts, and even state-of-the-art RuO2. X-ray photoelectron spectroscopy (XPS) analysis a transition of Mn, Fe, and Ni elements from metallic states to oxidation states, with surface dissolution of Cr after OER durability tests. This research elucidates the phase-dependent electrocatalytic performance and surface reconstruction in HEAs, providing valuable insights for designing and optimizing HEA materials for electrocatalytic applications.